2014
DOI: 10.3892/etm.2014.2032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tumor necrosis factor α-induced and nuclear factor κB-silenced LNCaP prostate cancer cells by RT-qPCR

Abstract: Prostate cancer is the second leading cause of morbidity and mortality in males in the Western world. In the present study, LNCaP, which is an androgen receptor-positive and androgen-responsive prostate cancer cell line derived from lymph node metastasis, and DU145, which is an androgen receptor-negative prostate cancer cell line derived from brain metastasis, were investigated. TNFα treatment decreased p105 and p50 expression and R1881 treatment slightly decreased p105 expression but increased p50 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…STAMP2 mRNA expression was significantly induced by all three cytokines in a dose-dependent manner (Figure 2a-c). Contrary to a previous report of negative results [35], TNF treatment of LNCaP cells led to a modest, but significant induction of STAMP2, although weaker if compared to the TNF-induced canonical NF-κB target gene IKBA (inhibitor of kappa B alpha) (Figure 2a). At the same concentration, TNF did not induce STAMP2 expression in C4-2B cells (Figure S1a).…”
Section: Temporal Regulation Of Stamp2 Expression By Cytokinescontrasting
confidence: 99%
“…STAMP2 mRNA expression was significantly induced by all three cytokines in a dose-dependent manner (Figure 2a-c). Contrary to a previous report of negative results [35], TNF treatment of LNCaP cells led to a modest, but significant induction of STAMP2, although weaker if compared to the TNF-induced canonical NF-κB target gene IKBA (inhibitor of kappa B alpha) (Figure 2a). At the same concentration, TNF did not induce STAMP2 expression in C4-2B cells (Figure S1a).…”
Section: Temporal Regulation Of Stamp2 Expression By Cytokinescontrasting
confidence: 99%
“…This expression has then been found to increase when the prostate is in a diseased state (Korkmaz et al, 2002;Porkka et al, 2002;Wang et al, 2010). Previous studies have found STEAP2 to be most highly expressed in LNCaP cells, with lower but still increased levels recorded in PC3 cells, which correlate with the results of this study (Figure 3.1; Gonen- Korkmaz et al, 2014;Porkka et al, 2002;Whiteland et al, 2014). Of the four prostate cancer cell lines assessed here, DU145 cells were the only cell line to exhibit lower levels of STEAP2 than the normal cell line PNT2, consistent with previous studies (Figure 3.1; Korkmaz et al, 2002;Porkka et al, 2002).…”
Section: Challitasupporting
confidence: 90%
“…In previous studies, STEAP2 overexpression has been induced either ectopically or by transfection in DU145 cells to monitor its effects in androgenindependent cells, further suggesting its expression in this cell line is relatively low (Gonen- Korkmaz et al, 2014;Wang et al, 2010). The highest significant increases in STEAP2 expression were found in androgen-sensitive prostate cancer cell lines; LNCaP and C4-2B, suggesting that AR signalling may play a role in its expression, hence the inclusion of the androgen-sensitive, LNCaPderived C4-2B cell line in this study.…”
Section: Challitamentioning
confidence: 99%
“…Western blot assays were performed according to previously described methods ( 10 , 11 , 13 ). Briefly, cMSCs were lysed with RIPA buffer containing phenylmethylsulfonyl fluoride (Sangon Biotech Co., Ltd.), then 50 µg total protein was quantitated using a BCA protein assay kit (P0009; Beyotime Institute of Biotechnology) and subjected to 6–10% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%